A Collection of Short Stories Dirawu Kelong by Ahmad Bakri (Structural Analysis) - Aisah, Nur; Permana, Ruswendi; Koswara, Dedi (International Journal of Language and Culture, 2024)
This research is titled “A Collection of Short Stories Dirawu Kelong by Ahmad Bakri (Structural Analysis).” It is motivated by the unique characteristics of Ahmad Bakri's works, especially in terms of story structure and language. One of Ahmad Bakri’s notable works is the Collection of Short Stories Dirawu Kelong. Based on this background, the study aims to analyze the story structure in the Collection of Short Stories Dirawu Kelong by Ahmad Bakri. The elements described include theme, characters, setting, plot, point of view, language style, and moral message. This research employs a descriptive method. Data was collected through literature study techniques. Selected data, namely the short story Dirawu Kelong, were analyzed using direct element analysis and structural analysis. The findings show that the theme of the short story is social; there are four characters; the plot follows a sequential structure; the setting includes daytime as the time and the kitchen and forest as places. The point of view is the first person; the language style is simple, and the moral message is that we should strive to be good children to everyone.